The gross face and virtual fame: semiotic mediation in Japanese virtual communication - Nozawa, Shunsuke (2012)
"This article examines an emerging art of self–fashioning and sociality in Japanese–language virtual communication. Through an ethnographic exploration I argue that crucial to the structure and experience of Japanese virtual communication are acts of opacity. People in the Japanese virtual mobilize elaborate techniques of material camouflage and anonymity to effectively conceal their body and obscure their identity. They are normatively faceless. I offer this ethnography to suggest that these acts of obfuscation, the presentation of the self–in–disguise in everyday life, force us to reorganize our own modernist epistemological framework. Treating acts of opacity in the Japanese virtual not as a question of presence, secrecy, and truth but instead as themselves a complex social project, this article aims to parse out competing ideologies of communication in the contemporary culture of media. I will address these ideologies as they inform a set of interconnected categories such as anonymity, privacy, and personhood, which are themselves deeply couched in modernist epistemological terms." [Information des Anbieters]
https://katalog.adlr.link/Record/finc-80-20481